The role of solvent swelling in the self-assembly of squalene based nanomedicines1. Issue 21 (7th June 2015) - Saha, Debasish; Testard, Fabienne; Grillo, Isabelle; Zouhiri, Fatima; Desmaele, Didier; Radulescu, Aurel; Desert, Sylvain; Brulet, Annie; Couvreur, Patrick; Spalla, Olivier
<x xml:space="preserve">Abstract</x> Squalene based nanoparticles obtained via nanoprecipitation are promising candidates as efficient anti-cancer drugs.